Beef stew - Brenner, Barbara; Siracusa, Catherine (New York : Random House, 1990)
When his friends decline to come over for a beef stew dinner, Nicky feels bad until a surprise visitor shows up.
Preschool-Grade 1.
260
Accelerated Reader AR
Keywords: Dinners and dining -- Fiction